Human Trafficking Is a Public Health Issue : A Paradigm Expansion in the United States - Chisolm-Straker, Makini; Stoklosa, Hanni (Springer International Publishing : Imprint: Springer, 2017)
This clear-sighted reference examines the public health dimensions of labor and sex trafficking in the United States, the scope of the crisis, and possibilities for solutions. Its ecological lifespan approach globally traces risk and protective factors associated with this exploitation, laying a roadmap towards its prevention. Diverse experts, including survivors, describe support and care interventions across domains and disciplines, from the law enforcement and judicial sectors to community health systems and NGOs, with a robust model for collaboration. By focusing on the humanity of trafficked persons, a public health paradigm broadens our understanding of and ability to address trafficking while adding critical direction and resources to the criminal justice and human rights structures currently in place. Among the topics covered: Children at Risk: Foster Care and Human Trafficking LGBTQ Youth and Vulnerability to Sex Trafficking Physical Health of Human Trafficking Survivors: Unmet Essentials Research Informing Advocacy: An Anti-Human Trafficking Tool Caring for Survivors Using a Trauma-Informed Care Framework The Media and Human Trafficking: Discussion and Critique of the Dominant Narrative Human Trafficking Is a Public Health Issue is a sobering read; a powerful call to action for public health professionals, including social workers and health care practitioners providing direct services, as well as the larger anti-trafficking community of advocates, prosecutors, taskforce members, law enforcement agents, officers, funders, and administrators. "An extraordinary collection of knowledge by survivors, academics, clinicians, and advocates who are experts on human trafficking. Human Trafficking is a Public Health Issue is a comprehensive offering in educating readers on human trafficking through a multi-pronged public health lens." Margeaux Gray: Survivor, Advocate, Artist, Public Speaker.
Keywords: Medicine.; Emergency medicine.; Public health.; Social justice.; Human rights.; elektronické knihy; electronic books